2019
DOI: 10.1590/0366-69132019653742543
|View full text |Cite
|
Sign up to set email alerts
|

Factorial design applied to sodium activation of a Brazilian bentonite

Abstract: Sodium bentonites are extensively used in industry because they have specific properties that are wanted for several purposes, such as high swelling, thixotropy, and cation exchange capacity. Otherwise, calcium and polycationic bentonites, which are predominant in Brazil, need to be chemically treated by sodium activation to expand their content of interlayer exchangeable sodium cations, which increases these properties. The present study shows the factorial design of the sodium activation for a polycationic b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…It was observed that natural clay presented CEC 4.95 ± 0.17 cmol/kg and that after activation it increased significantly ( p -value < 0.05) up to 42.64 ± 108 cmol/kg. That is, the treatment with NaCl allows the activation of the adsorption sites [ 36 ] due to the exchange of the divalent cation Ca 2+ and Al 3+ by the monovalent cation Na 1+ present in clays, thus improving the thixotropic behavior of clay in suspension and dispersion. This exchange can be represented using Equation (9) [ 37 ].…”
Section: Resultsmentioning
confidence: 99%
“…It was observed that natural clay presented CEC 4.95 ± 0.17 cmol/kg and that after activation it increased significantly ( p -value < 0.05) up to 42.64 ± 108 cmol/kg. That is, the treatment with NaCl allows the activation of the adsorption sites [ 36 ] due to the exchange of the divalent cation Ca 2+ and Al 3+ by the monovalent cation Na 1+ present in clays, thus improving the thixotropic behavior of clay in suspension and dispersion. This exchange can be represented using Equation (9) [ 37 ].…”
Section: Resultsmentioning
confidence: 99%
“…The bentonite used was an activated sodium bentonite, named Brasgel™ Bentonite, produced and supplied by Bentonit União Nordeste Ltd., sited in Boa Vista, PB. The term "activated" means that this material was processed to substitute the calcium, predominantly present in the natural Brazilian bentonite, for sodium [8]. The vermiculite used was an expanded vermiculite produced and supplied by Vermiculita Isolantes Termo-Acústicos Ltd., sited in Belo Horizonte, MG.…”
Section: Methodsmentioning
confidence: 99%